A multiscale network-based model of contagion dynamics: Heterogeneity, spatial distancing and vaccination - Maíra Aguiar; Giovanni Dosi; Damián A. Knopoff; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
Lockdown and vaccination policies have been the major concern in the last year in order to contain the SARS-CoV-2 infection during the COVID-19 pandemic. In this paper we present a model able to evaluate alternative lockdown policies and vaccination strategies. Our approach integrates and refines the multiscale model proposed by Bellomo et al. , 2020, analyzing alternative network structures and bridging two perspectives to study complexity of living systems. Inside dierent matrices of contacts we explore the impact of closures of distinct nodes upon the overall contagion dynamics. Social distancing is shown to be more effective when targeting the reduction of contacts among and inside the most vulnerable nodes, namely hospitals/nursing homes. Moreover, our results suggest that school closures alone would not signicantly affect the infection dynamics and the number of deaths in the population. Finally, we investigate a scenario with immunization in order to understand the effectiveness of targeted vaccination policies towards the most vulnerable individuals. Our model agrees with the current proposed vaccination strategy prioritising the most vulnerable segment of the population to reduce deaths.
Keywords: C6; D85; 330; Pandemic; COVID-19; epidemiological models; kinetic theory; active particles; spatial patterns; networks; vaccination; health policies